Lake Uluabat Point Pollutant Sources and Pollution Loads - Saadet Hacısalihoğlu; Feza Karaer (Doğal Afetler ve Çevre Dergisi)
In this study, flow values and pollution loads of point pollutant sources in Uluabat Lake basin were monitored in 4 different sampling points for 12 months in August 2013-July 2014 period and spatial and temporal changes of parameters were examined. The monitored parameters were suspended solids (SS), chemical oxygen demand (COD), biological oxygen demand (BOD), ammonium nitrogen (NH4-N), nitrate nitrogen (NO3-N), total nitrogen (TN), phosphate phosphorus (PO4-P) and total phosphorus (TP) parameters. As a result of the study, the average flow rate of Mustafakemalpaşa Stream (MKP Stream) was found to be 8.91 m3 /sec and Kocasu Stream was 19.72 m3 /sec. It was observed that the average flow rate values were higher than other point sources. Akçalar Creek is the point source with the lowest flow rate and the average flow rate is 0.03 m 3/sec. It was found that MKP Stream, which is the inlet stream to the lake, carries a high amount of pollution to the lake. When the pollution loads were evaluated, it was found that Akçalar Creek carries the least pollutant (TN:19.6 tons/year; TP:0.3 tons/year; KOI:74 tons/year; BOI:50.5 tons/year; AKM:41.4 tons/year), and Uluabat pumping station has the highest pollution load (TN:333.6 tons/year; TP:5.3 tons/year; KOI:1570 tons/year; BOI:662.5 tons/year; AKM:368.4 tons/year).